2018
DOI: 10.2147/ott.s180131
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 contributes to 5-FU resistance in gastric cancer by epigenetically suppressing FBXO32 expression

Abstract: BackgroundIncreasing evidence suggests the involvement of enhancer of zeste homologue 2 (EZH2) in chemoresistance of cancer treatment. Nevertheless, its function and molecular mechanisms in gastric cancer (GC) chemoresistance are still not well elucidated.Materials and methodsIn the present study, we investigated the functional role of EZH2 in 5-fluorouracil (5-FU) resistance of GC cells and discovered the underlying molecular mechanism.ResultsResults revealed that EZH2 was upregulated in 5-FU-resistant GC tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…We found through UCSC (http://genome.ucsc.edu/) that NDRG2 promoter contains potential binding sites for EZH2 (Figure 3B). EZH2 is defined as a histone methyltransferase, which can induce histone H3K27me3 on the promoter to result in epigenetic silence of genes (Kim and Roberts, 2016; Wang et al, 2018; Xu et al, 2018). It has been widely reported that lncRNAs could epigenetically repress gene expression by recruiting EZH2 (Zhang and Peng, 2017; Ma et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found through UCSC (http://genome.ucsc.edu/) that NDRG2 promoter contains potential binding sites for EZH2 (Figure 3B). EZH2 is defined as a histone methyltransferase, which can induce histone H3K27me3 on the promoter to result in epigenetic silence of genes (Kim and Roberts, 2016; Wang et al, 2018; Xu et al, 2018). It has been widely reported that lncRNAs could epigenetically repress gene expression by recruiting EZH2 (Zhang and Peng, 2017; Ma et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We predicted via searching UCSC and confirmed through ChIP assay that EZH2 bound to NDRG2 promoter. It is axiomatically known that EZH2 can regulate histone H3K27me3 on the promoter of genes, so as to repress the gene expression (Kim and Roberts, 2016; Wang et al, 2018; Xu et al, 2018). Accordingly, our study first revealed that UNC5B‐AS1 interacted with EZH2 to target NDRG2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RPL11, ribosomal protein L11; TP53, Tumor protein p53; 5-FU, 5-fluorouracil; si, small interfering RNA. poor prognosis of gastric cancer patients (27). Although further investigation is needed, gastric cancer patients with both high RPL11 expression and low EZH2 expression may show higher sensitivity against 5-FU treatment than those with either high RPL11 or low EZH2 expression alone, which may help to more accurately predict 5-FU sensitivity in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression was clearly downregulated in oral cancer cell lines following miR-629-3p transfection. It has been reported to contribute to CDDP resistance in urothelial cancer and 5-fluorouracil (5-FU) resistance in gastric cancer [21,22]. FBXO32, which is one of the candidates but not confirmed by qRT-PCR, is known to be related to drug resistance.…”
Section: Discussionmentioning
confidence: 99%